The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1365-2605.1978.tb00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Sugars: A Biochemical Approach to the Control of Male Fertility

Abstract: 6‐Chloro‐6‐deoxyglucose (120 μmol; 24 mg kg b.wt.), 6‐chloro‐6‐deoxyfructose (< 240 μ 48 mg/kg b.wt.), 6‐chloro‐6‐deoxysucrose (240 μmol; 85 mg/kg b.wt.), ′6‐chloro‐′6‐deoxysucrose (< 240 μmol; 85 mg/kg b.wt.) and 6.′6‐dichloro‐6,′6‐dideoxysucrose (240 μmol; 89 mg/kg b.wt.) administered to male rats daily, by oral gavage, render them infertile after 7 days treatment. The effect is sustained through at least 4 weeks of treatment and is reversed 3 to 6 weeks after treatment is withdrawn. Spermatozoa from the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…However, the energy charge was identical to that found in monkey ejaculated spermatozoa (Hoskins et al, 1971) and similar to that observed in rat epididymal spermatozoa after incubation with glucose for 10 min (Ford & Waites, 1978).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the energy charge was identical to that found in monkey ejaculated spermatozoa (Hoskins et al, 1971) and similar to that observed in rat epididymal spermatozoa after incubation with glucose for 10 min (Ford & Waites, 1978).…”
Section: Discussionsupporting
confidence: 84%
“…However, high doses of -chlorohydrin are required to inhibit the oxidation of acetate, pyruvate or lactate by ram spermatozoa (Brown-Woodman et al, 1978). Moreover, spermatozoa from rats treated with 6-chloro-6-deoxyglucose (24 mg/kg/day), which has an antifertility effect similar to that of -chlorohydrin (Ford & Waites, 1978), can remain motile and retain a high energy charge when supplied with 2 mM-pyruvate plus 4 mM-DL-lactate as substrates although these parameters decline rapidly when 2 mM-glucose is the only substrate given (Ford & Waites, 1980). Therefore, unless spermatozoa are compelled to metabolize sugar at some stage, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When spermatozoa from the cauda epididymidis of the treated rats were incubated in the presence of 2 mM uI4 C-D glucose, they oxidized only 10% as much glucose as spermatozoa from controls, and the levels of ATP and total adenine nucleotide content fell rapidly [18]. These biochemical effects are associated with a rapid decline in cell motility and fertility.…”
Section: Energy Metabolism and Sperm Motilitymentioning
confidence: 98%
“…Other agents with an epididymal site of action followed including cyproterone acetate and the 6-deoxy-6-halo sugars [21,22]. Although in animal studies antifertility effects could be reached in as little as 1 week from onset of dosing, toxicity or variable efficacy precluded further development of these agents [23][24][25].…”
mentioning
confidence: 95%